More certainty in uncertainty: a special life-cycle approach for management decisions in volatile markets - Marcel Röser (Journal of Management Control, 2024)
Risk managers as corporate stewards are important gatekeepers in enterprises and they are essential to managing risks. Relatedly, a more accurate evaluation of the risk factors allows a well-founded decision-making process and reduces the number of surprising situations that could occur especially in volatile markets. Forward-looking risk management increases entrepreneurial resilience because risk factors are already estimated at an earlier stage in the corresponding risk analysis. Furthermore, the range of potential solutions can be estimated in a successive way. These aspects are relevant especially for products with follow-up effects. Such~new product bundles are typical in current businesses. They require a more precise risk analysis, which allows an effective view of the life-cycles of the whole products and the customer relationships. Within well-founded risk decomposition, the existing risk can be managed appropriately. The following study presents a special life-cycle approach for evaluating products and customers in risky situations. Especially for important management decisions, such an approach is necessary, given that only a few products or customers can have a major influence on the success of the enterprise. Therefore, a systematic risk-oriented approach is essential that adequately identifies, assesses and controls the risk factors and enables agile adaptability for fast changes. Considering the risk management perspective, simulation techniques are a useful approach to solve sophisticated decision situations. The applicability of this concept is demonstrated using a computation example reflecting real-world circumstances. The presented approach is broadly defined. That is the reason why the approach can also~be transferred to~other sectors.
Keywords: D81; M11; M40; M41; 330; Risk management; Risk factors; Uncertainty; Resilience; Life-cycle analysis; Decision-making; Volatile markets